An Analysis on Language Learning Strategies Used by Successful Language Learners in Speaking: A Narrative Inquiry on Three English Department Students - Chaerunnisa, Alifia (Universitas Terbuka, 2023)
This study aimed to investigate the learning strategies employed by proficient language learners in the context of speaking skills. It also delved into the challenges these learners encountered and the strategies they employed to overcome them. The study enlisted three fifth-semester students from the English Education Department at a university in Surakarta as participants. Employing a qualitative approach, specifically narrative inquiry, the research collected data through observations, interviews, and questionnaires. The researcher observed each participant's speaking class three times, meticulously documenting their strategies and challenges. The findings revealed that the successful language learners' use of specific learning strategies significantly enhanced their language acquisition process. Additionally, the participants encountered various obstacles in their English learning journey, yet demonstrated an impressive ability to effectively address these challenges, thus shedding light on the resilience and adaptability of successful language learners. This study contributes valuable insights for educators and learners striving to excel in language acquisition.